Differences in surface roughness of nanohybrid composites immersed in varying concentrations of citric acid - Gabriela Kevina Alifen; Adioro Soetojo; Widya Saraswati (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The surface roughness of restoration is important in predicting the length of time it might remain in the mouth. Conditions within the oral cavity can affect the surface roughness of a restoration. Nanohybrid composite is widely used in dentistry because it can be applied to restore anterior and posterior teeth. Athletes routinely consume isotonic drinks which are acidic and even more erosive than the carbonated variety because they contain a range of acids; the highest content of which being citric acid. Purpose: The aim of the study was to analyze the surface roughness of nanohybrid composite after having been subjected to immersion in varying concentrations of citric acid. Methods: Two isotonic drinks (Pocari Sweat and Mizone) were analyzed using high performance liquid chromatography (HPLC) to quantify the respective concentrations of citric acid which they contained. A total of 27 samples of cylindrical nanohybrid composite were prepared before being divided into three groups. In Group 1, samples were immersed in citric acid solution derived from Pocari Sweat. Those of Group 2 were immersed in citric acid solution derived from Mizone; while Group 3, samples were immersed in distilled water as a control. All samples were immersed for 7 days, before their surface roughness was tested by means of a surface roughness tester (Mitutoyo SJ-201). Data was analyzed using a one-way ANOVA test. Results: The results showed that there was no significant difference in surface roughness between Groups 1, 2 and 3 (p=0.985). Conclusion: No difference in surface roughness of nanohybrid composites results from prolonged immersion in varying concentrations of citric acid.